Cognitive-Behavioral Therapy for Anxiety in Elementary School Students - Emine Gül Kapçý; Runa Ýdil Uslu; Denis Sukhodolsky; Derya Atalan-Ergin; Gökçe Çokamay (Bilişsel Davranışçı Psikoterapi ve Araştırmalar Dergisi)
Objective: The study examined the effectiveness of a school-based cognitive-behavioral therapy (CBT) program for school aged children with high levels of anxiety symptoms. Method: The study design was a randomized controlled trial (RCT) comparing CBT to a waitlist-control condition. A total of 61 children (37 girls and 24 boys; age range 8-13) with high scores on either self-report or parental reports of anxiety participated in the study. The treatment group received 10 weekly sessions over three months that was administered using the Cool Kids treatment manual (Lyneham 2003). Outcome measures included parent-rated scales of anxiety and anxiety interference, and child self-report scales of anxiety, anxiety interference, depression and self-esteem. Both study groups were comparable at baseline for clinical and demographic variables. A mixed design ANOVA with pre-post treatment as within and CBT vs waitlist groups as between group variable was used for statistical analysis. Results: At post-test, CBT group had lower scores on anxiety, interference of anxiety and depression scales and higher scores on self-esteem scales of scholastic competence, social acceptance and behavioral conduct, but not physical appearance and athletic ability compared to the waitlist control group. Conclusions: The study presents empirical evidence for the effectiveness of a school based CBT Cool Kids program for reducing anxiety symptoms and increasing self-esteem in elementary school children. Future studies may examine the durability of treatment gains. [JCBPR 2012; 1(2.000): 121-126]